Reimagining the library of the future : public buildings and civic space for tomorrow's knowledge society - Lehmann, Steffen, 1963- (2022)
"It takes a critical look at the history, present, and future transformation of this significant building typology that has recently emerged as a redefined community place, social condenser, and urban incubator for knowledge generation, storage, and sharing. In particular, the library has evolved as a vibrant and vital member of community development and as a basis for outreach efforts...This book presents 40 recent public and academic libraries from around the world, with over 200 images. As the survey of precedents shows, the historical cases have informed the design of the recent libraries and the continuous development of the building type over time. Well-designed libraries are now in abundance, and the wider view of this study includes mediatheques and learning centers. The selection of contemporary projects focuses on urban libraries in Europe (Germany, Italy, Austria, Netherlands), the US, Canada, Mexico, Australia, Japan, and China." - Page 4 of cover.
Includes bibliographical references (pages 232-235) and index.
Keywords: 2000-2099; Library architecture; Libraries -- Designs and plans; Library buildings -- Designs and plans; Architecture, Modern -- 21st century; Library buildings; Libraries; Architecture, Modern; Library architecture; Architectural drawings; Architectural drawings